Photo-thermal synergistic curing resin, glass fiber composite material and preparation method of glass fiber composite material
By adding a network connecting agent to the resin matrix, the interaction between the photocured acrylate network and the thermally cured epoxy resin network is promoted, and the problem of low deep curing efficiency of existing photocuring methods is solved, and the mechanical properties of glass fiber laminates are significantly improved.
Patent Information
- Application Number
- CN202411898837.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-18
AI Technical Summary
The existing photocuring methods are inefficient during deep curing, resulting in poor mechanical properties of glass fiber composites. The method based on photothermal dual curing relies on heat transfer capabilities and is not efficient.
Adding a network linking agent with acrylate groups and epoxy groups to the resin matrix promotes the covalent interaction between the photocured acrylate network and the thermally cured epoxy resin network, and improves the compatibility of the polymer network.
The bending strength and bending modulus of the glass fiber laminate are significantly improved, the bending strength can be increased by more than 30%, and the resin composition is light-shielded and stored at 25°C, and has good stability.
Smart Images

Figure CN119638902A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer composite materials and light-curing materials, and in particular to a method for preparing a high-performance acrylate-epoxy matrix glass fiber composite material cured by near infrared. Background Art
[0002] Glass fiber fabric reinforced polymer matrix composites (GFRPC) are considered to be an ideal substitute for existing metal matrix materials due to their high specific modulus, light weight and high strength. The manufacturing method of GFRPC is generally heat curing, which relies on large-scale hot pressing equipment or hot drying ovens, so that its production and processing can generally only be carried out in factories. Radiation curing technology is more valuable in on-site construction and emergency repair due to its high efficiency, economy, and in-situ curing.
[0003] However, due to the light absorption of the matrix chemical substances and the deflection of the light path by the glass fiber, the UV-based photocuring method makes it difficult to cure the deep matrix, resulting in low curing efficiency, insufficient effective curing thickness, and poor mechanical properties. Existing methods are often solved based on dual photothermal curing. One is to heat and cure after photocuring, but this method is not separated from the heating equipment and cannot reflect the advantages of photocuring. Another method relies on the thermal effect of the curing reaction and the light source, and uses free radicals to promote cationic polymerization. This method strongly relies on the heat transfer ability of the material itself, and has low curing efficiency in glass fiber materials with low thermal conductivity. The matrix resin used in the photothermal curing method in the prior art is often a mixture of acrylate and epoxy resin, which will produce two polymer networks after curing. However, due to the thermodynamic incompatibility of the polymer network, the matrix phase separation occurs, thereby reducing the mechanical properties of the matrix.
[0004] Therefore, it is necessary to develop a new resin material and develop high-performance composite materials based on this resin. Summary of the invention
[0005] In view of the above problems existing in the prior art, the present invention specifically adds a network connector having polymerization-active acrylate and glycidyl ether into the hybrid resin matrix to promote the connection of the two cross-linked networks to obtain a composite material with better performance.
[0006] The first aspect of the present invention is to provide a photothermal synergistic curing resin composition, comprising the following raw materials in parts by weight:
[0007]
[0008]
[0009] Furthermore, the network connector contains an acrylate structure and a glycidyl ether structure that can undergo polymerization reaction;
[0010] In some embodiments of the present invention, the network connector is selected from one or a combination of 4-hydroxybutyl acrylate glycidyl ether, methacrylate glycidyl ether, and acrylate glycidyl ether.
[0011] The photothermal synergistic curing resin composition uses acrylate-epoxy resin as a matrix composition.
[0012] In some embodiments of the present invention, the acrylic resin is selected from one or a combination of epoxy-modified acrylic esters, polyurethane acrylic esters, and polyester acrylic esters.
[0013] In some embodiments of the present invention, the acrylate monomer is selected from one or a combination of isobornyl acrylate, hydroxyethyl acrylate, cyclotrimethylolpropane formal acrylate, dicyclopentadiene acrylate, and dicyclopentadiene diacrylate.
[0014] In some embodiments of the present invention, the epoxy resin is selected from one or a combination of industrial-grade bisphenol A epoxy resin and bisphenol F epoxy resin F.
[0015] In some embodiments of the present invention, the photoinitiator is selected from one or a combination of photoinitiator 819, photoinitiator 784, and photoinitiator TPO.
[0016] In some embodiments of the present invention, the latent imidazole curing agent is selected from one or a combination of 1-ethyl-3-methylimidazolium acetate, 3-ethyl-1-methylimidazolium sulfonate, and 1-butyl-3-methylimidazolium chloride.
[0017] In some embodiments of the present invention, the amount of various chemical components in the photothermal synergistic curing resin composition is as follows: 28% to 74% acrylate resin; 4% to 24% acrylate monomer; 16% to 45% epoxy resin; 2% to 5% network connector; 0.5% to 1.5% photoinitiator; 0.5% to 3% upconversion particles; and 3% to 7% latent imidazole curing agent.
[0018] The second aspect of the present invention is to provide a method for preparing the photothermal synergistic curing resin composition, comprising the following steps:
[0019] S11. The acrylate resin, acrylate monomer, epoxy resin, network connector, photoinitiator, and upconversion particles are weighed in a mass ratio and added to a ball mill;
[0020] S12. The ball mill is placed in an oven at 50-65°C for a period of time to reduce the viscosity of the resin and dissolve the photoinitiator;
[0021] S13. Add the ball mill beads to the hot-baked ball mill and fully homogenize in a high-speed disperser while hot;
[0022] S14. Cool the homogenized formula to room temperature, add latent imidazole curing agent, homogenize again and store in a dark place.
[0023] In one embodiment, in step S12, the treatment is performed in an environment of 50-65° C. for 30 minutes.
[0024] In a preferred embodiment, the light-heat synergistically curable resin composition prepared in step S14 is stored in a dark place under refrigerated conditions.
[0025] The third aspect of the present invention is to provide a glass fiber laminate, which is made of the light-heat synergistically curable resin composition and glass fiber fabric. The bending strength of the glass fiber laminate is significantly improved.
[0026] In some embodiments of the present invention, the flexural strength of the fiberglass laminate is increased by more than 30%.
[0027] A fourth aspect of the present invention is to provide a method for preparing the glass fiber laminate, comprising steps S21, S22, and S23;
[0028] S21. Coating a photothermosetting resin matrix, covering the glass fiber fabric,
[0029] S22. Repeat step S21 until the desired thickness or number of layers;
[0030] S23. After vacuum degassing, the glass fiber laminate is obtained by irradiation curing under a near-infrared light source.
[0031] In some embodiments of the present invention, the vacuum degassing device is a degassing bag;
[0032] Furthermore, the wavelength of the near-infrared light source is 965-995 nm. In a preferred embodiment, 980 nm near-infrared light is used.
[0033] In some embodiments of the present invention, the preparation method of the glass fiber laminate is specifically prepared in the following steps: 1. Cut the PET vacuum bag film into a suitable size, and paste the vacuum glue around the vacuum bag film, and apply a layer of release agent in the middle. 2. Apply the above-prepared photothermal curing resin matrix in the center of the vacuum bag film, cover it with a layer of glass fiber fabric, and after compaction, apply a layer of resin matrix on the surface of the glass fiber fabric again, and repeat several times until the designed number of glass fiber fabric layers is reached. 3. Cover the stacked glass fiber fabrics with release cloth and guide net in turn, and paste the guide tube and spiral tube on the vacuum glue, and finally cover it with a layer of vacuum bag film and seal it to form a vacuum bag system. 4. Connect the guide tube to the diaphragm pump to evacuate air to remove excess air and resin in the vacuum bag, and finally seal the guide tube to obtain a laminate pre-cured material. 5. Irradiate under a 980nm near-infrared light source (14.6W / cm 2 ) for 90s to obtain a glass fiber laminate.
[0034] Beneficial effects:
[0035] (1) The present invention first provides a photothermal synergistically curable resin composition; a "network connector" having an acrylate group at one end and an epoxy group at another end is added to the resin matrix, so that the photocurable acrylate network and the thermally curable epoxy resin network are connected through covalent interaction, thereby promoting the compatibility of the two polymer networks and significantly improving the mechanical properties of the material;
[0036] (2) The present invention also provides an application of the resin composition for preparing a glass fiber laminate; the flexural strength and flexural modulus of the prepared glass fiber laminate are significantly improved, and the flexural strength can be increased by 30%;
[0037] (3) The present invention also provides a method for preparing the glass fiber laminate, wherein the curing light source uses near-infrared light, which directly initiates deep light curing by utilizing its high penetrating power, and generates heat in situ inside the glass fiber composite material to initiate thermal curing, without the need for an additional post-curing step; the method for preparing the glass fiber laminate of the present invention has a simple process and is suitable for industrial production;
[0038] (4) The photothermal synergistic curing resin composition prepared by the present invention is stored in a dark place at 25° C., ensuring that the epoxy resin is stable for more than 40 days, has good stability, and does not need to be stored in a refrigerator. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] The accompanying drawings are used to provide a further understanding of the present application and constitute a part of the specification. Together with the embodiments of the present application, they are used to explain the present application and do not constitute a limitation to the present application.
[0040] Figure 1 It is a curing principle diagram of the resin composition prepared by the present invention;
[0041] Figure 2 is a dynamic mechanical analysis (DMA) graph of a laminate prepared from the resin composition obtained in Examples and Comparative Examples;
[0042] Figure 3 Deep curing performance test of the resin compositions prepared in Comparative Example 1 and Example 1;
[0043] Figure 4 The storage stability test of the resin composition prepared in Examples 1-4 was conducted. DETAILED DESCRIPTION
[0044] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0045] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0046] Deep curing performance test of resin composition:
[0047] Deep curing: Use a tool with dimensions of 3×3×2.2 cm 2 The grooved PTFE mold is cut into 2.5×2.5cm pieces of fiberglass fabric. 2 16 layers of glass fiber fabric were added to the mold and the resin matrix was poured in. The mold was then placed in a vacuum oven for degassing. 980nm near-infrared irradiation (17.4W / cm 2 ) was irradiated for 90 s to obtain a deep-cured composite material.
[0048] Storage stability test of resin composition:
[0049] The resin composition was placed in a constant temperature oven at 25° C. At regular intervals, 400 μL of sample was taken out with a pipette, and the viscosity of the resin matrix at a shear frequency of 50 r / s was measured with a rotational rheometer, and the data was recorded.
[0050] Fiberglass laminate performance test:
[0051] 1. Basic performance test of glass fiber laminate. Use Barcol hardness tester to measure the hardness of laminate surface. Use ablation method and drainage method to test the density and fiber volume fraction of laminate.
[0052] 2. DMA and phase separation test. Cut the glass fiber laminate into 4×1×0.2cm 3The sample block was used to measure the change of tanδ of the sample at 40-200℃ in the oscillation mode.
[0053] 3. Bending strength test. Cut the fiberglass laminate into 9×1.5×0.2cm 3 The bending strength of the sample was tested by three-point bending mode of a universal testing machine. The loading rate was set to 1 mm / min and the span was 4 cm.
[0054] Embodiment 1:
[0055] In one embodiment, the amounts of the components of the resin matrix are as follows:
[0056]
[0057] The specific preparation steps are:
[0058] 1. Weigh 12.6g of RY1101, 5.4g of dicyclopentadiene diacrylate, 12g of epoxy resin E51, 0.9g of network connector glycidyl methacrylate, 0.18g of photoinitiator 819, and 0.9g of upconversion particles and add them into a ball mill;
[0059] 2. Place the ball mill in a 60°C oven for 30 minutes to reduce the viscosity of the resin and dissolve the photoinitiator.
[0060] 3. Add 2 zirconium oxide ball milling beads to the hot-dried ball mill, put it into the high-speed disperser while it is hot and fully homogenize it, and control the speed at 1000r / min.
[0061] 4. Cool the homogenized formula to room temperature, add 2 g of 1-ethyl-3-methylimidazolium acetate, and homogenize again using a high-speed disperser (1000 r / min). After completion, put it in the refrigerator for later use.
[0062] Embodiment 2:
[0063] In one embodiment, the amounts of the components of the resin matrix are as follows:
[0064]
[0065] The specific preparation steps are:
[0066] 1. Weigh 12.6g of RY1101, 5.4g of dicyclopentadiene diacrylate, 12g of epoxy resin E51, 0.68g of network connector glycidyl methacrylate, 0.18g of photoinitiator 819, and 0.9g of upconversion particles and add them into a ball mill;
[0067] 2. Place the ball mill in a 60°C oven for 30 minutes to reduce the viscosity of the resin and dissolve the photoinitiator.
[0068] 3. Add 2 zirconium oxide ball milling beads to the hot-dried ball mill, put it into the high-speed disperser while it is hot and fully homogenize it, and control the speed at 1000r / min.
[0069] 4. Cool the homogenized formula to room temperature, add 2 g of 1-ethyl-3-methylimidazolium acetate, and homogenize again using a high-speed disperser (1000 r / min). After completion, put it in the refrigerator for later use.
[0070] Embodiment 3:
[0071] In one embodiment, the amounts of the components of the resin matrix are as follows:
[0072]
[0073] The specific preparation steps are:
[0074] A method for preparing an acrylate-epoxy resin matrix with a network connector, the specific preparation steps are:
[0075] 1. Weigh 12.6g of RY1101, 5.4g of dicyclopentadiene diacrylate, 12g of epoxy resin E51, 1.74g of network connector glycidyl methacrylate, 0.18g of photoinitiator 819, and 0.9g of upconversion particles and add them into a ball mill;
[0076] 2. Place the ball mill in a 60°C oven for 30 minutes to reduce the viscosity of the resin and dissolve the photoinitiator.
[0077] 3. Add 2 zirconium oxide ball milling beads to the hot-dried ball mill, put it into the high-speed disperser while it is hot and fully homogenize it, and control the speed at 1000r / min.
[0078] 4. Cool the homogenized formula to room temperature, add 2 g of 1-ethyl-3-methylimidazolium acetate, and homogenize again using a high-speed disperser (1000 r / min). After completion, put it in the refrigerator for later use.
[0079] Embodiment 4:
[0080] In one embodiment, the amounts of the components of the resin matrix are as follows:
[0081]
[0082]
[0083] The specific preparation steps are:
[0084] 1. Weigh 16.8g of RY1101, 7.2g of dicyclopentadiene diacrylate, 6g of epoxy resin E51, 0.9g of network connector glycidyl methacrylate, 0.18g of photoinitiator 819, and 0.9g of upconversion particles and add them into a ball mill;
[0085] 2. Place the ball mill in a 60°C oven for 30 minutes to reduce the viscosity of the resin and dissolve the photoinitiator.
[0086] 3. Add 2 zirconium oxide ball milling beads to the hot-dried ball mill, put it into the high-speed disperser while it is hot and fully homogenize it, and control the speed at 1000r / min.
[0087] 4. Cool the homogenized formula to room temperature, add 2 g of 1-ethyl-3-methylimidazolium acetate, and homogenize again using a high-speed disperser (1000 r / min). After completion, put it in the refrigerator for later use.
[0088] Comparative Example 1
[0089] In a comparative example, the amounts of the components of the resin matrix are as follows:
[0090]
[0091] The specific preparation steps are:
[0092] 1. Weigh 112.6g of RY110, 5.4g of dicyclopentadiene diacrylate, 112g of epoxy resin E51, 0.18g of photoinitiator 819, and 0.9g of upconversion particles and add them into a ball mill;
[0093] 2. Place the ball mill in a 60°C oven for 30 minutes to reduce the viscosity of the resin and dissolve the photoinitiator.
[0094] 3. Add 2 zirconium oxide ball milling beads to the hot-dried ball mill, put it into the high-speed disperser while it is hot and fully homogenize it, and control the speed at 1000r / min.
[0095] 4. Cool the homogenized formula to room temperature, add 2 g of 1-ethyl-3-methylimidazolium acetate, and homogenize again using a high-speed disperser (1000 r / min). After completion, put it in the refrigerator for later use.
[0096] Comparative Example 2
[0097] In one embodiment, the amounts of the components of the resin matrix are as follows:
[0098]
[0099] The specific preparation steps are:
[0100] 1. Weigh 16.8g of RY1101, 7.2g of dicyclopentadiene diacrylate, 16g of epoxy resin E5, 0.18g of photoinitiator 819, and 0.9g of upconversion particles and add them into a ball mill;
[0101] 2. Place the ball mill in a 60°C oven for 30 minutes to reduce the viscosity of the resin and dissolve the photoinitiator.
[0102] 3. Add 2 zirconium oxide ball milling beads to the hot-dried ball mill, put it into the high-speed disperser while it is hot and fully homogenize it, and control the speed at 1000r / min.
[0103] 4. Cool the homogenized formula to room temperature, add 2 g of 1-ethyl-3-methylimidazolium acetate, and homogenize again using a high-speed disperser (1000 r / min). After completion, put it in the refrigerator for later use.
[0104] Test example:
[0105] Stability test: The light-heat synergistic curing resin composition prepared in Examples 1-4 was stored in a dark place at 25 degrees Celsius to test its stability. The results showed that under this condition, it could be stable for more than 40 days without affecting the performance of the resin.
[0106] The preparation method of the glass fiber laminated board, the specific preparation steps are as follows:
[0107] (1) Cut the PET vacuum bag film into a suitable size, stick the vacuum adhesive around the vacuum bag film, and apply a layer of release agent in the middle.
[0108] (2) Cut the glass fiber fabric into 11×8cm 2 The rectangle is ready for use.
[0109] (3) The photothermosetting resin matrix prepared in Example 1 is coated on the center of the vacuum bag film, and then covered with a layer of glass fiber fabric. After compaction, another layer of resin matrix is coated on the surface of the glass fiber fabric. This process is repeated multiple times until 5 layers of glass fiber fabric are laid.
[0110] (4) The stacked glass fiber fabrics are covered with a release cloth and a guide net in turn, and a guide tube and a spiral tube are attached to the vacuum glue. Finally, a layer of vacuum bag film is covered and sealed to form a vacuum bag system.
[0111] (5) Connect the guide tube to a diaphragm pump to remove excess air and resin in the vacuum bag, and finally seal the guide tube to obtain a pre-cured laminate. Irradiate under a 980nm near-infrared light source (14.6W / cm 2 ) for 90s to obtain a glass fiber laminate.
[0112] The specific steps for preparing laminates using the resin compositions prepared in other embodiments and comparative examples are the same as those in Experimental Example 1, the only difference being that the resin compositions prepared in the corresponding embodiments are used.
[0113] The performance test results of the laminates prepared from the resin compositions of the embodiments and comparative examples are shown in Table 1.
[0114] Table 1
[0115]
[0116] As shown in Table 1, the top hardness and bending strength of the resin compositions prepared in Examples 1-4 are significantly higher than those in Comparative Examples 1-2. Compared with Comparative Example 1, the bending strength of Example 1 is increased by 33.6%; and the top hardness is increased by 16.4%.
[0117] Figure 1 This is a schematic diagram of the curing principle of the resin composition of the present invention. Adding a small amount of network connector can effectively improve the cross-linking degree of the two resins, promote the compatibility of the two polymer networks, and improve the mechanical properties of the material.
[0118] like Figure 2 As shown in the (dynamic mechanical analysis diagram of the laminate), the cured products formed in Comparative Examples 1 and 2 both have two obvious tanδ peaks, indicating that phase separation has occurred in the matrix; as shown in the data of Comparative Example 2, two obvious tanδ peaks are exhibited at 110°C and 150°C. However, in Examples 1-4 where a network connector is added, only one tanδ peak is present, and the glass transition temperature of the material changes from two to one, indicating that phase separation has disappeared, proving that the network connector effectively promotes the fusion of the two polymer networks.
[0119] like Figure 3 As shown, both resin matrices are capable of curing glass fiber composites with a thickness of more than 15 mm.
[0120] like Figure 4 As shown, the photothermal synergistic curing resin composition prepared in Examples 1-4 has a viscosity below 10 Pa·s during a storage time of 960 h, indicating good storage stability.
[0121] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. A photothermal synergistic curing resin composition, characterized in that: The invention comprises the following raw materials in parts by weight: The network connector has an acrylate group at one end and contains an epoxy group.
2. The photothermal synergistic curing resin composition according to claim 1, characterized in that: The acrylate resin is selected from one or a combination of epoxy-modified acrylates, polyurethane acrylates, and polyester acrylates; And / or, one or a combination selected from 4-hydroxybutyl acrylate glycidyl ether, methacrylate glycidyl ether, and acrylate glycidyl ether.
3. The photothermal synergistic curing resin composition according to claim 1, characterized in that: The acrylate monomer is selected from one or a combination of isobornyl acrylate, hydroxyethyl acrylate, cyclotrimethylolpropane formal acrylate, dicyclopentadiene acrylate, and dicyclopentadiene diacrylate.
4. The photothermal synergistic curing resin composition according to claim 1, characterized in that: The epoxy resin is selected from one or a combination of industrial-grade bisphenol A epoxy resin and bisphenol F epoxy resin.
5. The photothermal synergistic curing resin composition according to claim 1, characterized in that: The photoinitiator is selected from one or a combination of photoinitiator 819, photoinitiator 784, and photoinitiator TPO.
6. The photothermal synergistic curing resin composition according to claim 1, characterized in that: The latent imidazole curing agent is selected from one or a combination of 1-ethyl-3-methylimidazolium acetate, 3-ethyl-1-methylimidazolium sulfonate, and 1-butyl-3-methylimidazolium chloride.
7. The method for preparing the photothermal synergistic curing resin composition according to any one of claims 1 to 6, characterized in that: The following steps are involved: S11. The acrylate resin, acrylate monomer, epoxy resin, network connector, photoinitiator, and upconversion particles are weighed in a mass ratio and added to a ball mill; S12. Treat the system in an environment of 50-65°C for 20-60 min; S13. Add the ball mill beads to the hot-baked ball mill and fully homogenize them in a high-speed disperser while hot; S14. Cool the homogenized formula to room temperature, add latent imidazole curing agent, homogenize again and store in a dark place.
8. A glass fiber laminate, characterized in that: The invention is made of the photothermal synergistically curable resin composition according to any one of claims 1 to 6 and glass fiber fabric.
9. The method for preparing the glass fiber laminate according to claim 8, characterized in that: The method comprises steps S21, S22 and S23; S21. Coating a photothermosetting resin matrix, covering the glass fiber fabric, S22. Repeat step S21 until the desired thickness or number of layers; S23. After vacuum degassing, the glass fiber laminate is obtained by irradiation curing under a near-infrared light source.
10. The preparation method according to claim 9, characterized in that: The vacuum degassing device is a degassing bag; the wavelength of the near-infrared light source is 965-995nm.
Citation Information
Patent Citations
Photo-thermal double-curing resin composition, prepreg and 3D printing method
CN108948279A
Photo-thermal double-curing 3D printing resin composition
CN108948280A
Near-infrared photothermal synergistic curing fiber composite prepreg and preparation method thereof
CN115636966A
Method for Preparing a Simultaneous Interpenetrating Network Comprising Epoxy and Vinyl Polymers for Epoxy Thermosets with Extended Outdoor Ultraviolet Weatherability
US20180194936A1